(untitled) (Fiep Bulletin - online, 2011)
This article, composed of fragments of my dissertation for the Master’s degree in Education, deals with the area of Physical Education knowledge, against a background of knowledge and learning used by the generalist teacher who gives classes in this subject. The results of this study indicate the insecurity experienced by these teachers as they give classes related to an area of knowledge for which they do not have a specific academic background, which leads to teaching based on intuition and on practical knowledge arising from experience.